Identification of Volatile Compounds in Lemon, Local Lemon and Lime Peel Extract Using Gas Chromatography – Mass Spectrometer - Ihsan Pratama, Muhammad; Yulianis, Yulianis; Sanuddin, Mukhlis (Media Farmasi: Jurnal Ilmu Farmasi, 2025)
Orange peel is one of the main sources of essential oil. Lemon orange can also be found in an area of Jambi City, commonly referred to as local lemon, but the shape and characteristics differ slightly from common lemons. The identification results of local lemon peels indicate that these oranges are a cross between lemons and limes (Citrus medica × Citrus aurantifolia). This study aims to analyze and determine the differences in the components of the peels of lemon, local lemon, and lime using gas chromatography–mass spectrometer (GC-MS). The contribution of this research lies in providing scientific data on the chemical composition of local lemon peels, which have not been widely studied, thereby offering potential applications for the development of natural products, essential oil industries, and local biodiversity utilization. This research was conducted by extracting the peels from lemons, local lemons, and limes using acetone as a solvent. The extracts were then analyzed for their components using GC-MS. The GC-MS analysis of acetone extracts from lemon, local lemon, and lime peels revealed 19 compounds in each sample. Four compounds were found to be common across all three samples, namely 2-pentanone, 4-hydroxy-4-methyl; β-bisabolene; bis (2-ethylhexyl) phthalate; and 2H-1-Benzopyran-2-one, 5,7-dimethoxy. Meanwhile, 15 other compounds showed different contents, indicating that the hybrid nature of local lemons influenced their chemical composition. These findings highlight the unique characteristics of local lemon peels and their potential as a valuable source of bioactive compounds.